A Qualitative Study Identifying Barriers and Facilitators of Physical Activity in Rural Communities. (23rd June 2019) - Gilbert, Amanda S.; Duncan, Dixie D.; Beck, Alan M.; Eyler, Amy A.; Brownson, Ross C.
Abstract : Background . Physical activity (PA) rates are lower in rural populations, compared to urban and suburban counterparts. Since PA is shown to decrease the risk of cancers and chronic diseases, increasing PA in rural environments is an important disease-prevention strategy. However, in order to develop effective interventions for rural populations, more research is needed. The purpose of the study was to elicit rural residents' thoughts and perceptions related to PA and walking trail use. Methods . Key informant interviews were conducted via telephone, with 62 adults, living in six rural communities in southeast Missouri, who identified as stakeholders, walking trail users, and nontrail users. Participants were recruited through word of mouth and snowball sampling. Interviews were digitally audio-recorded, transcribed, and qualitatively analyzed. Findings . Analysis revealed variation within the rural population, with each town unique in what constituted barriers and facilitators to PA. Life priorities other than physical health were found to be important motivators to PA and also influenced how PA was obtained. Community size was found to impact community resources and infrastructure, although this was mitigated by poverty rates. Conclusion . Rural communities are distinct from one another with different views and approaches to PA. Future interventions designed to increase PA should be mindful of differences at the individual and town levels and avoid a one-size-fits-all approach. Interventions would benefit from insight and support from community members and stakeholders, to facilitate a tailored approach to increase PA.